Relationship between Vascular Resistance and Sympathetic Nerve Fiber Density in Arterial Vessels in Children With Sleep Disordered Breathing. Issue 7 (17th July 2017) - Kontos, Anna; Lushington, Kurt; Martin, James; Schwarz, Quenten; Green, Ryan; Wabnitz, David; Xu, Xiangjun; M. Sokoya, Elke; Willoughby, Scott; Baumert, Mathias; Ferrante, Antonio; La Forgia, Melissa; et al.
Abstract : Background: Sleep disordered breathing in children is associated with increased blood flow velocity and sympathetic overactivity. Sympathetic overactivity results in peripheral vasoconstriction and reduced systemic vascular compliance, which increases blood flow velocity during systole. Augmented blood flow velocity is recognized to promote vascular remodeling. Importantly, increased vascular sympathetic nerve fiber density and innervation in early life plays a key role in the development of early‐onset hypertension in animal models. Examination of sympathetic nerve fiber density of the tonsillar arteries in children undergoing adenotonsillectomy for Sleep disordered breathing will address this question in humans. Methods and Results: Thirteen children scheduled for adenotonsillectomy to treat sleep disordered breathing underwent pupillometry, polysomnography, flow‐mediated dilation, resting brachial artery blood flow velocity (velocity time integral), and platelet aggregation. The dorsal lingual artery (tonsil) was stained and immunofluorescence techniques used to determine sympathetic nerve fiber density. Sympathetic nerve fiber density was correlated with increased resting velocity time integral ( r =0.63; P <0.05) and a lower Neuronal Pupillary Index ( r =−0.71, P <0.01), as well as a slower mean pupillary constriction velocity (mean, r =−0.64; P <0.05). A faster resting velocity time integral was associated with a slower peak pupillary constriction velocity ( r =−0.77; P <0.01) and higher platelet aggregation to collagen antigen ( r =0.64; P <0.05). Slower mean and peak pupillary constriction velocity were associated with higher platelet aggregation scores ( P <0.05; P <0.01, respectively). Conclusions: These results indicate that sympathetic activity is associated with change in both the function and structure of systemic vasculature in children with sleep disordered breathing.